Teachers' Discourse, Language, Genetics, Life Sciences, South Africa, classrooms - Mupfawa, Shungu (University of the Witwatersrand, Johannesburg, 2024)
South Africa has consistently ranked close to the bottom in international studies on the quality of mathematics and science education. This poor performance portrays a negative picture of the quality of teaching and learning science and mathematics in the country. Local reports such as the South African National Diagnostic Report on grade 12 performance attest to this as it shows that the quality of passes in life sciences at the matric level is low. As a result, fewer matriculants enrol for life sciences-related careers at higher institutions of learning. The overall quality of passes in life sciences could be aggravated by the poor performance of learners in genetics-related questions which make a substantial contribution to scores in the Life Sciences examination. Literature on the teaching and learning of genetics also points to difficulty with the teaching and learning of this topic, including the use of language by the teachers. This thesis reports on a case study in which I investigated the classroom Discourse of four life sciences teachers while teaching basic genetics to grade 12 learners. The study aimed to characterise the teachers’ Discourse during the teaching of basic genetics. In this study, my conception of Discourse was influenced by Gee’s Theory of Discourse which makes a distinction between Discourse with an upper-case ‘D’ denoting language and other factors associated with it and discourse with a lower-case ‘d’ as referring to language. Therefore, in this study, the teachers’ Discourse ‘D’ was conceptualised in terms of language ‘d’ (the language of science) and context which entailed Discourse strategies, interaction patterns, teacher Discourse moves, and multimodal representations. This study drew on literature and research from the fields of Discourse analysis, language, teacher talk, science teaching, and classroom Discourse to develop a complex picture of the classroom. A case study was conducted in three high schools in Johannesburg, South Africa. Data was collected from four teachers each of whom was observed three times, and video recorded while teaching basic genetics concepts to grade 12 learners. A follow-up interview was conducted with each teacher. These post-observation interviews together with field notes were added for data triangulation purposes. The interviews helped me to access teachers’ rationale for taking certain actions during the observed lessons. Moreover, the interviews enhanced the trustworthiness of my analysis. The lesson observation transcripts were analysed using Lemke’s Thematic Analysis merged with Mortimer and Scott’s Communicative Approaches and Discourse patterns. This study unveiled two major types of Discourse of teachers who followed an examination based approach and teachers whose Discourse followed a conceptual approach. This led to the development of a Discourse Teaching Strategy Model which portrays teachers as being either conceptually or assessment focused. My Discourse Teaching Strategy Model shows that amongst other characteristics, conceptually focused teachers used higher-order questions to build conceptual understanding and logical exposition for consolidation. Further, the model shows that logical exposition was sometimes replaced by selective summary where the teachers justified the curriculum. Teachers adopting a conceptual focused strategy used controlling pacing and marking importance as pedagogical measures and admonition for maintaining discipline. This study contributes to the effective teaching of genetics by offering the Discourse Teaching Strategy Model as a model to guide thinking about the planning and development of science teaching as well as a tool for reflection upon one’s teaching strategies. Thus, this model can be used to expand self-development or in-service development especially if one is to teach for ii conceptual understanding. Researchers can use the model as an analytical tool for identifying a particular teacher’s Discourse practices.
A research report submitted in fulfillment of the requirements for a Doctor of Philosophy, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Teachers’ Discourse; Language; Genetics; Life Sciences; South Africa; Classrooms; SDG-4: Quality education